2015
DOI: 10.1103/physrevb.91.184205
|View full text |Cite
|
Sign up to set email alerts
|

Structural disorder versus chiral magnetism inCr1/3NbS2

Abstract: The crystal structure of a disordered form of Cr 1/3 NbS2 has been characterized using diffraction and inelastic scattering of synchrotron radiation. In contrast to the previously reported symmetry (P6322), the crystal can be described by a regular twinning of an average P63 structure with three disordered positions of the Cr ions. Short-range correlations of the occupational disorder result in a quite intense and structured diffuse scattering; a static nature of the disorder was unambiguously attributed by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 47 publications
5
27
1
Order By: Relevance
“…Figure 1(b) shows the temperature dependence of the magnetization for several values of magnetic field. We can see characteristic cusp structures near the transition temperature; a similar cusp has been observed in experiments [10,15,20,22] and has been obtained in a phenomenological theory [16]. Small step-like structures at low temperatures are due to the finite-size effect along the helical axis.…”
Section: A 3dmf Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Figure 1(b) shows the temperature dependence of the magnetization for several values of magnetic field. We can see characteristic cusp structures near the transition temperature; a similar cusp has been observed in experiments [10,15,20,22] and has been obtained in a phenomenological theory [16]. Small step-like structures at low temperatures are due to the finite-size effect along the helical axis.…”
Section: A 3dmf Resultssupporting
confidence: 84%
“…The analysis of this model has revealed characteristic magnetization curves, which have been observed in experiments on CrNb 3 S 6 [9,10,[20][21][22] and YbNi 3 Al 9 [13][14][15]. Temperature effect of the spin moment has been included phenomenologically [5,16] and magnetization, entropy and specific heat have been discussed.…”
Section: Introductionmentioning
confidence: 85%
“…This result implies that disorder in Cr subsystem and small nonequality in occupancy of the 2c and 2d Wyckoff sites (model II) cannot be completely excluded. Contrary to the previous works on M 1=3 NbX 2 , 13,21,24,25 we found that in Cr 1=3 NbSe 2 , Cr atoms are predominantly distributed over 2b Wyckoff site. Such a discrepancy may be associated with enhanced covalency of the Se bonds formed with Cr in comparison with the Cr-S bonds in Cr 1=3 NbS 2 .…”
Section: Discussioncontrasting
confidence: 99%
“…9,28 However, contrary to the result of our refinement for Cr 1=3 NbSe 2 all the crystal structure studies for M 1=3 NbX 2 reported predominant occupation of the 2c Wyckoff site by M atoms. 13,21,24,25 Detailed inspection of the refined atomic coordinates obtained for model II makes us doubt that the crystal structure of Cr 1=3 NbSe 2 is truly non-centrosymmetric. Indeed in accordance with Ref.…”
Section: B Neutron Diffraction Above Curie Temperaturementioning
confidence: 99%
See 1 more Smart Citation